Proteins that accumulate with age in human skeletal-muscle aggregates contribute to declines in muscle mass and function in Caenorhabditis elegans - Srinivas Ayyadevara; Meenakshisundaram Balasubramaniam; Pooja Suri; Samuel G. Mackintosh; Alan J. Tackett; Dennis H. Sullivan; Robert J. Shmookler Reis; Richard A. Dennis (2016)
Protein aggregation increases with age in normal tissues, and with pathology and age in Alzheimer's hippocampus and mouse cardiac muscle.We now ask whether human skeletal muscle accumulates aggregates with age.Detergent-insoluble protein aggregates were isolated from vastus lateralis biopsies from 5 young (23-27 years of age) and 5 older (64-80 years) adults.Aggregates, quantified after gel electrophoresis, contain 2.1-fold more protein (P<0.0001)when isolated from older subjects relative to young.Of 515 proteins identified by liquid chromatography coupled to tandem mass spectrometry, 56 (11%) were significantly more abundant in older muscle, while 21 (4%) were depleted with age (each P<0.05).Orthologs to seven of these proteins were then targeted in C. elegans by RNA interference.Six of the seven knockdown treatments decreased protein aggregation (range 6-45%, P<0.01 to <0.0001) and increased muscle mass (range 1.5-to 1.85fold, P<0.01 to <0.0001) in aged nematodes, and rescued mobility (range 1.4 to 1.65-fold, P≤0.0005 each) in a nematode amyloidopathy model.We conclude that specific aggregate proteins, discovered as differentially abundant in aging human muscle, have orthologs that contribute functionally to aggregation and age-associated muscle loss in nematodes, and thus can be considered potential drug targets for sarcopenia in humans.